2023
DOI: 10.3390/mi14030518
|View full text |Cite
|
Sign up to set email alerts
|

A Compact UWB Monopole Antenna with Triple Band Notches

Abstract: This article presents an ultra-wideband (UWB) monopole antenna with triple band notch characteristics. The proposed antenna consists of an octagonal patch, fed with a 50 Ω line, which occupies a compact size of 40 mm × 29 mm (0.36λ × 0.26λ, λ is computed using 2.7 GHz frequency) and resonances at a relatively low frequency (2.94 GHz). Specifically, an L-shaped stub, an inverted C-shaped slot, and a pair of U-shaped resonating structures are introduced into the design, which allow antenna to generate three band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Up to now, much effort has been made in the development of flexible/wearable antennas with notch properties, and a variety of notch techniques have been adopted, such as etching various shaped slot on the radiating patch 11 17 or ground plane incorporation of electric ring resonator (ERR) 18 , split ring resonators (SRRs) 11 , 19 22 or complementary split ring resonators (CSRRs) 23 26 , using parasitic elements 27 , 28 , defected ground structures (DGS) 29 31 and EBG resonators 32 35 , etc. For instance, Geyikoglu et al 29 demonstrated the design and implementation of a flexible UWB antenna with dual-band rejection capabilities for wearable biomedical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, much effort has been made in the development of flexible/wearable antennas with notch properties, and a variety of notch techniques have been adopted, such as etching various shaped slot on the radiating patch 11 17 or ground plane incorporation of electric ring resonator (ERR) 18 , split ring resonators (SRRs) 11 , 19 22 or complementary split ring resonators (CSRRs) 23 26 , using parasitic elements 27 , 28 , defected ground structures (DGS) 29 31 and EBG resonators 32 35 , etc. For instance, Geyikoglu et al 29 demonstrated the design and implementation of a flexible UWB antenna with dual-band rejection capabilities for wearable biomedical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Octagonal patch size of 40 mm × 29 mm is designed to get UWB from 2.70 GHz to 11.06 GHz. Specifically, an L-shaped stub, an inverted C-shaped slot, and a pair of U-shaped resonating structures are introduced into the design, which allow antenna to generate three band notches at 3.22-3.83 GHz, 4.49-5.05 GHz, and 7.49-8.02 GHz, corresponding to WiMAX band and Indian National Satellite (INSAT) band [12]. On the two C-shaped arms and the slots of the rectangular patch, pin diodes are utilized.…”
Section: Introductionmentioning
confidence: 99%